Strobilanthes erecta (Acanthaceae), a newly recorded species from China and Vietnam - Thanh Son, Nguyen; Lin, Zheli; Nguyen, Sinh Khang; Deng, Yunfei (Phytotaxa, 2018)
Strobilanthes erecta C. B. Clarke is reported as a newly recorded species from Vietnam and China. Examination of type material revealed that Goldfussia laotica and Strobilanthes suborbicularis are conspecific with S. erecta. In addition, the pollen morphology, line drawing and distribution map of S. erecta are provided.